Divergence of perspectives on women and higher education leadership? In conversation with men in leadership - Moodly, A. L. (South African Journal of Higher Education, 2021)
Literature on the challenges and marginalisation of women in higher education and leadership has focused mostly on the voices of women in understanding their experiences. The structural and cultural milieu of the higher education landscape has continuously been put forward as part of a complexity of contributing factors to the challenges. In exploring literature, the author found little that brings men’s voices to the discourse. Seeking the voices of men in leadership, was with the understanding that in occupying positions of power and influence, they are strategically positioned and have agency in transforming the structural and cultural milieu. The article focuses on challenges experienced by women on a trajectory to the highest levels of higher education leadership, and engages with men’s perspectives on the higher education structural and cultural milieu. The focus is on areas that women have highlighted as barriers within this milieu. The article engages with the conversations with men, including vice chancellors, undertaken as part of a research project, to explore whether there is a common view and understanding of the higher education environment and women’s experiences and challenges in this context. Further, whether men in leadership exercise their agency in influencing and challenging the status quo. The article concludes that though there may not necessarily be a divergence in perspectives regarding the milieu and women’s experiences therein, this may only be at an empirical/observed level. The deeper, underlying structures and mechanisms that retain the status quo have neither been recognised nor engaged. There is also the danger of complacency and lack of exercising agency in disrupting the status quo, which may contribute to the lack of change. The findings also foreground a wrestling with a myriad of challenges as experienced within the higher education sector, contributing to the lack of prioritising a focus on women towards leadership.